Study of Performance Index and Business Analysis on Chicken Infected by Escherichia coli with Probiotic Provision of Lactic Acid Bacteria - Abdurrahman, Farid; Soeharsono, Soeharsono; Soepranianondo, Koesnoto (Jurnal Medik Veteriner, 2022)
This study was conducted to determine the performance index and business analysis of broilers infected with Escherichia coli by administering lactic acid bacteria probiotics in the form of Lactoped® (Lactobacillus casei, Lactobacillus plantarum, Lactobacillus fermentatum, Lactobacillus acidophilus). This type of research was true experimental research using a post-test-only control group design. The design used in this study was a completely randomized design (CRD). 30 broilers were randomized into three treatments (P0, P1 and P2) in each group with a minimum of six times. Probiotic lactic acid bacteria (LAB) with a concentration of 108 CFU/ml in broilers infected with Escherichia coli showed a higher performance index. It could cover the entire fixed costs so still feasible to do, meanwhile, for the scale of research (10 heads/treatment), it was not yet feasible to implement due to it has suffered losses.